2000
DOI: 10.1021/jp002113a
|View full text |Cite
|
Sign up to set email alerts
|

Model Structures and Electron Density Distributions for the Silica Polymorph Coesite at Pressure:  An Assessment of OO Bonded Interactions

Abstract: The crystal structure and the bond critical point, bcp, properties of the electron density distribution for the high-pressure silica polymorph coesite were generated for pressures up to ∼17 GPa, using first-principles calculations. The nonequivalent SiO bond lengths and the SiOSi and OSiO angles of the generated structures agree with those observed to within ∼1%. With compression, the SiO bond lengths and the variable SiOSi angles of the structures both decrease while the value of the electron density, ρ(r c),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
7
24
0
Order By: Relevance
“…The rate of compression of the four other Si-O-Si angles ( Figure 7 ), with the smaller angles being more compressible, is in good agreement with the experimental studies at lower pressures [6,7] . The ab initio calculations [8] suggest compressional rates similar to those obtained in all of experiments, although the calculated angles appear to be smaller than those measured. Decrease of the smallest Si1-O5-Si2 angle from 137.44 ° (ambient, Angel et al [7] ) to 125.54 ° at ∼ 20 GPa contributes to the shortening along the b -axis.…”
Section: Mechanisms Of Compressionsupporting
confidence: 75%
See 1 more Smart Citation
“…The rate of compression of the four other Si-O-Si angles ( Figure 7 ), with the smaller angles being more compressible, is in good agreement with the experimental studies at lower pressures [6,7] . The ab initio calculations [8] suggest compressional rates similar to those obtained in all of experiments, although the calculated angles appear to be smaller than those measured. Decrease of the smallest Si1-O5-Si2 angle from 137.44 ° (ambient, Angel et al [7] ) to 125.54 ° at ∼ 20 GPa contributes to the shortening along the b -axis.…”
Section: Mechanisms Of Compressionsupporting
confidence: 75%
“…Due to this arrangement there are five distinct Si-O-Si angles in the structure. The high-pressure structural behavior of coesite was previously studied using in-house based single crystal X-ray diffraction up to 5.2 GPa [6] and up to 8.7 GPa [7] in ethanol-methanol pressure medium, as well as by means of ab initio calculations up to 17 GPa [8] . These studies concluded that the symmetry of the unit cell appears less hexagonal with increasing pressure, compressing in the a direction more than twice as much than in the c direction.…”
Section: Introductionmentioning
confidence: 99%
“…[2a,d, 12k,o] Braga et al [17] also presented convincing evidence on the repulsive AA and CC interactions in crystalline KHC 2 O 4 . Gibbs et al [18] questioned the existence of bonding interactions between the tetrahedral oxide anions in silica polymorph coesite. In their opinion, the occurrence of BPs and (3,-1) CPs (bond critical points (BCPs)) between these anions is most likely not due to the bonding interactions between the…”
mentioning
confidence: 99%
“…The main objective of this study will be to examine the bonded radii for bonded pairs of atoms comprising a number of oxide crystals and to explore the connection between the radii, the S&P ionic and crystal radii, and the experimental M–O interatomic distances. It will be of particular interest to learn the extent for which the ED distribution of the oxide atom is polarized and its radius contracted by the bonded atoms.…”
Section: Proposed Studymentioning
confidence: 99%